Efficient defluoridation of drinking water using mesoporous magnetic malachite nanocomposites - Amna Sarwar; Jin Wang; Nadia Riaz; Muhammad Saqib Khan; Ajmal Khan; Rafaqat Ali Khan; Afnan Jan; Anar Gojayev; Ahmed Al-Harrasi; Qaisar Mahmood (Cleaner Engineering and Technology)
The study evaluated the efficacy of magnetic mesoporous Malachite nanoparticles (NPs) in eliminating fluoride (F−) from drinking water. Screening experiments were conducted to gauge the F− adsorption capabilities of the synthesized material under different Fe3O4 loading conditions. Among the various nanomaterials examined, 0.25-Fe-M demonstrated optimal performance, exhibiting consistent Fe3O4 distribution with a crystal size of 16.66 nm with revealed irregular morphology exhibiting magnetic properties, a surface area of 13.595 m2/g and a pore size of 1.6574 nm. The optimized reaction conditions determined were: 10 min of contact time, a NC dose of 0.5 mg/mL, and an F− concentration of 10 mg/L. The maximum adsorption capacities recorded were 6.57 mg/g for Fe3O4 NPs and 7.87 mg/g for malachite NPs. Notably, the optimal adsorption capacity for F− removal was achieved with 0.25 Fe-M-NCs, reaching 8.44 mg/g, demonstrating superior performance compared to other NCs. The interplay between surface area, pore volume, and adsorption is intricate and contingent upon the unique properties of the adsorbent and adsorbate, with specific interactions governing the adsorption process. Furthermore, this study unveiled accelerated adsorption with shorter contact time and high adsorption capacity at the working pH.